Artificial intelligence's interpretation of the neuroanatomical aspect of Peter Paul Rubens's copy of "The Battle of Anghiari" by Leonardo da Vinci. (June 2023) - Keshelava, Grigol
We tested to see how Ruben's copy of "The Battle of Anghiari" by Leonardo da Vinci would be interpreted by AI in a neuroanatomical aspect. We used WOMBO Dream, an artificial intelligence (AI)-based algorithm that creates images based on words and figures. The keyword we provided for the algorithm was "brain" and the reference image was Ruben's drawing. AI interpreted the whole drawing as a representation of the brain. The image generated by the algorithm was similar to our interpretation of the same painting.